2008
DOI: 10.1007/s10815-008-9254-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful twin birth following blastocyst culture of embryos derived from the immotile ejaculated spermatozoa from a patient with primary ciliary dyskinesia: A case report

Abstract: Purpose To describe the ultrastructure of spermatozoa from a patient with complete asthenozoospermia that resulted in live births following blastocyst culture. Materials and methods Analyses of spermatozoa from a 36 year old patient were performed using light and electron microscopy. The hypo-osmotic swelling test was used to select spermatozoa for intracytoplasmic sperm injection. Embryos were cultured to the blastocyst stage. Results 100% of the spermatozoa had dynein arm deficiency with secondary defects va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…To summarize, this a rare report of a twin pregnancy [5,8,11,13] in a Kartagener patient. What makes it unique is that it is the first case showing a certain resistance to conventional sperm selection procedures.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…To summarize, this a rare report of a twin pregnancy [5,8,11,13] in a Kartagener patient. What makes it unique is that it is the first case showing a certain resistance to conventional sperm selection procedures.…”
Section: Discussionmentioning
confidence: 81%
“…With respect to this, HOS test was found to be helpful since several authors reported pregnancies after selection based on osmotic behavior of the sperm membrane which allows estimating sperm viability [9,11,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The severity of symptoms and the age at which the condition is diagnosed is quite variable. 7,8 Progression of the disease in KS is variable.…”
Section: Discussionmentioning
confidence: 99%